Immunology of ocular allergy - Zierhut, Manfred; Biedermann, Tilo; Ono, Santa Jeremy (New Delhi : Jaypee Brothers Medical Publishers, 2010)
Este libro examina las reacciones inmunológicas de la alergia ocular en comparación con las enfermedades alérgicas de la piel, revisa los avances recientes en la fisiopatología de la alergia ocular y resume el conocimiento clínico actual y las estrategias de tratamiento.
This book examines the immunologic reactions of ocular allergy in comparison to allergic skin diseases, reviews recent advances in the pathophysiology of ocular allergy and summarizes current clinical knowledge and treatment strategies.
Contents 1. Mast cell and innate immunity 2. An evolving view on the (Patho) physiology of inmunoglobulin E 3. B-Cells and allergy 4 Dendritic and T Cells 5. Eosinophlis y otros 14 capítulos más
Keywords: ENFERMEDADES DE LOS OJOS -- ASPECTOS INMUNOLÓGICOS; INMUNOLOGÍA OCULAR; EYE DISEASES